Shame and honor : a vulgar history of the Order of the Garter - Trigg, Stephanie (University of Pennsylvania Press, 2012)
"It's a nice piece of pageantry. . . . Rationally it's lunatic, but in practice, everyone enjoys it, I think."-HRH Prince Philip, Duke of EdinburghFounded by Edward III in 1348, the Most Noble Order of the Garter is the highest chivalric honor among the gifts of the Queen of England and an institution that looks proudly back to its medieval origins. But what does the annual Garter procession of modern princes and politicians decked out in velvets and silks have to do with fourteenth-century institutions? And did the Order, in any event, actually originate in the wardrobe malfunction of the traditional story, when Edward held up his mistress's dropped garter for all to see and declared it to be a mark of honor rather than shame? Or is this tale of the Order's beginning nothing more than a vulgar myth?With steady erudition and not infrequent irreverence, Stephanie Trigg ranges from medieval romance to Victorian caricature, from imperial politics to medievalism in contemporary culture, to write a strikingly original cultural history of the Order of the Garter. She explores the Order's attempts to reform and modernize itself, even as it holds onto an ambivalent relationship to its medieval past. She revisits those moments in British history when the Garter has taken on new or increased importance and explores a long tradition of amusement and embarrassment over its formal processions and elaborate costumes. Revisiting the myth of the dropped garter itself, she asks what it can tell us about our desire to seek the hidden sexual history behind so venerable an institution.Grounded in archival detail and combining historical method with reception and cultural studies, Shame and Honor untangles 650 years of fact, fiction, ritual, and reinvention.